Leaf wettability, anatomy and ultra-structure of Nothofagus antarctica and N. betuloides grown under a CO2 enriched atmosphere - Bahamonde, Héctor A.; Aranda García, Ismael; Peri, Pablo L.; Gyenge, Javier; Fernández, Victoria (Plant Physiology and Biochemistry, 2023)
9 Pág. Increasing CO2 air concentration may affect wettability, anatomy and ultra-structure of leaves of Patagonian forest species, evergreen and deciduous plants potentially responding differently to such CO2 increases. In this study, we analysed the wettability, anatomy and ultra-structure of leaves of Nothofagus antarctica (deciduous) and N. betuloides (evergreen) grown under high CO2 concentrations. Leaf wettability was affected by increasing CO2, in different directions depending on species and leaf side. In both species, soluble cuticular lipid concentrations per unit leaf area raised with higher CO2 levels. Stomatal parameters (density, size of guard cells and pores) showed different responses to CO2 increasing depending on the species examined. In both species, leaf tissues showed a general trend to diminish with higher CO2 concentration. Cuticle thickness was modified with higher CO2 concentration in N. betuloides, but not in N. antarctica leaves. In both species, chloroplasts were often damaged with the increase in CO2 concentration. Our results show that several surface and internal leaf parameters can be modified in association with an increase in atmospheric CO2 concentration which may very among plant species. This work was supported by the National Institute of Agricultural Technology (INTA), Argentina. Peer reviewed